Primary Burkitt Lymphoma of the Fourth Ventricle in an Immunocompetent Young Patient - Abdulrahman Alabdulsalam; Syed Z. A. Zaidi; Imran Tailor; Yasser Orz; Sadeq Al-Dandan (Case Reports in Pathology)
Primary Burkitt lymphoma of the central nervous system (CNS) is rare, with only few cases reported in the literature. An 18 year-old immunocompetent male presented with multiple cranial nerves palsies and was found to have a mass predominantly in the 4th ventricle of the brain. Tumor was surgically removed and showed morphological and immunohistochemical features consistent with Burkitt lymphoma. The patient responded very well to anthracycline based chemotherapy with high dose methotrexate (HD MTX) and intrathecal (IT) chemotherapy delivered by Ommaya reservoir. Primary Burkitt lymphoma of the CNS is a rare entity that poses differential diagnostic challenge with other small round blue cell tumors.